DIGITALISASI LAYANAN KEUANGAN SYARIAH DALAM MENINGKATKAN INKLUSI KEUANGAN - Nur'aini, Umul (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
The digitalization of financial services has become a crucial strategy in expanding public access to financial services, including within the Islamic finance sector. This study aims to analyze the role of Islamic financial service digitalization in enhancing financial inclusion and to examine its conformity with the principles of Islamic economics. This research employs a qualitative approach using a library research method, drawing on scholarly books, national and international journal articles, as well as official reports from Islamic financial institutions and relevant authorities. Data analysis was conducted through content analysis using a descriptive-analytical approach. The findings indicate that the digitalization of Islamic financial services—such as Islamic mobile banking, Islamic financial technology (fintech), and digital payment systems based on Sharia-compliant contracts—significantly contributes to increasing financial inclusion, particularly among unbanked and underbanked populations. Moreover, this digital transformation aligns with the objectives of maqashid al-shari’ah, especially in safeguarding wealth (hifz al-mal) and promoting economic justice. Nevertheless, challenges related to digital literacy, Sharia compliance, and data security remain critical issues that require serious attention. This study concludes that the digitalization of Islamic financial services serves as a strategic instrument in strengthening an inclusive financial system grounded in Sharia values.